2014
DOI: 10.1364/josab.31.000450
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear characterization of robust multimaterial chalcogenide nanotapers for infrared supercontinuum generation

Abstract: We present the results of an investigation of the nonlinear characteristics of a new class of robust, multimaterial, allsolid chalcogenide nanotapers prepared from high-index-contrast chalcogenide fibers. The fiber is drawn from a preform produced by multimaterial coextrusion and consists of chalcogenide core and cladding (which dictate the optical properties) and a built-in thermally compatible polymer jacket that provides mechanical stability to the fibers and nanotapers. We measure the nonlinear refractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…The Abouraddy group at Creol showed that dual layer chalcogenide nanotapers can be integrated into a thermoplastic polymer jacket ( Figure 17 a). [ 148 ] The dispersion engineering has been achieved via tapering the structure down to a remaining chalcogenide core diameter of only 500 nm over a length of 50 mm, allowing the generation of broadband light over an octave-spanning spectral bandwidth when pumped with femtosecond pulses (center pulse wavelength: 1.55 µm, pulse energies ≈ 40 pJ).…”
Section: Nonlinear Light Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…The Abouraddy group at Creol showed that dual layer chalcogenide nanotapers can be integrated into a thermoplastic polymer jacket ( Figure 17 a). [ 148 ] The dispersion engineering has been achieved via tapering the structure down to a remaining chalcogenide core diameter of only 500 nm over a length of 50 mm, allowing the generation of broadband light over an octave-spanning spectral bandwidth when pumped with femtosecond pulses (center pulse wavelength: 1.55 µm, pulse energies ≈ 40 pJ).…”
Section: Nonlinear Light Generationmentioning
confidence: 99%
“…Adapted. [ 148 ] Copyright 2014, OSA. b) Mid-IR modulation instability observed in a As 2 Se 3 / polymer microwire.…”
Section: Nonlinear Light Generationmentioning
confidence: 99%
“…However, it has already been shown that the fabrication of very small diameter robust chalcogenide fibers (called "nanotapers") is possible [33]. For example, Shabahang et al have demonstrated robust chalcogenide tapers with diameter as small as 0.25 μm [34]. One way to make the fiber robust to mechanical perturbations is to coat the fiber with a polymer protection layer.…”
Section: Introductionmentioning
confidence: 99%
“…Chalcogenide materials exhibit 1 high transparency in the mid-IR spectral region, high refractive indices (from 2.0 to 3.5) and a high nonlinear refractive index n 2 reaching 3-5×10 -18 m 2 /W. Thus, they are very good candidates for applications in light amplifiers, optical regenerators, and for broadband radiation sources in the mid-IR based on supercontinuum generation and other applications [1][2][3][4][5][6][7][8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%